1996
DOI: 10.4315/0362-028x-59.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Trichinellosis in Pigs by Artificial Digestion and Enzyme Immunoassay

Abstract: The objective of this study was to demonstrate the reliability of current and proposed methods for the inspection of swine and other species for infection with the parasite Trichinella spiralis. Five groups of pigs were infected with doses of 2500, 500, 100, 50, and 20 T. spiralis larvae to establish moderate and low-level infections. Pigs were bled periodically during the study for samples to be tested by enzyme immunoassay (EIA). At the conclusion of the study, pigs were slaughtered and tissues collected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 0 publications
4
61
0
Order By: Relevance
“…O utbreed laboratory mice (Ssc: CF1) and farm bred red foxes (Vulpes vulpes) were orally inoculated with nine different Trichinella genotypes (doses: 500 larvae/mouse and 10.000 larvae/fox) obtained from the Trichinella Reference Centre (Rome) (Pozio et al, 1989 to six weeks of storage the muscle larvae (ML) were recovered from the meat samples by digestion according to Gamble (1996). A control sample (day 0) was digested immediately after mincing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…O utbreed laboratory mice (Ssc: CF1) and farm bred red foxes (Vulpes vulpes) were orally inoculated with nine different Trichinella genotypes (doses: 500 larvae/mouse and 10.000 larvae/fox) obtained from the Trichinella Reference Centre (Rome) (Pozio et al, 1989 to six weeks of storage the muscle larvae (ML) were recovered from the meat samples by digestion according to Gamble (1996). A control sample (day 0) was digested immediately after mincing.…”
Section: Methodsmentioning
confidence: 99%
“…to six weeks of storage the muscle larvae (ML) were recovered from the meat samples by digestion according to Gamble (1996). A control sample (day 0) was digested immediately after mincing.…”
Section: T He Nematodes In the Genusmentioning
confidence: 99%
“…Distribution of T. spiralis larvae in each tissue sample was determined by digestion of 100 g of tissue (Gamble, 1996).…”
Section: Digestion Testingmentioning
confidence: 99%
“…Literature data confirm the value of E-S ELISA for the detection of trichinellosis in pigs (Gamble et al 1983, Smith 1987, Smith 1988, Smith and Snowdon 1989, van der Leek et al 1992, Nöckler et al 1995, Gamble 1996, Gamble 1998, Kapel et al 1998, Reiterová et al 1999, Kapel and Gamble 2000, Nöckler et al 2005, Kořínková et al 2008). The authors of the studies cited above applied the E-S ELISA to detect experimental swine trichinellosis induced by varying infection doses of T. spiralis larvae (50, 100, 200, 500, 1000, 1500, 3000, 5000, 8000, 10 000, 15 400, 20 000, 64 000).…”
Section: Introductionmentioning
confidence: 75%
“…Our findings indicate that the highest intensity of T. spiralis infection occurred in the diaphragm. A large number of authors have identified swine diaphragm and tongue as equally valuable research material for T. spiralis muscle larvae detection (Kotula et al 1984, Gamble 1996, Forbes and Gajadhar 1999, Serrano et al 1999. In the present study T. spiralis infection intensity averaged to 24.30 larvae/g in the tongue, which was significantly lower (53%) than in the diaphragm (46.18 larvae/g = 100%).…”
Section: Discussionmentioning
confidence: 99%